A qualitative analysis of psychosocial needs and support impacts in families affected by young sudden cardiac death: The role of community and peer support. (1st December 2020) - Steffen, Edith Maria; Timotijevic, Lada; Coyle, Adrian
Abstract : Background: Young sudden cardiac death (YSCD), often occurring in previously healthy individuals, is a tragic event with devastating impact on affected families, who are at heightened risk of posttraumatic stress and prolonged grief and may themselves be at risk of YSCD. Previous research suggests that surviving family members' psychosocial support needs are often unmet. Purpose: This study sought to identify how YSCD-affected families experience dedicated community and peer support in light of their psychosocial support needs. Methods: The study used a qualitative design, employing a thematic analysis of focus group and interview data. Three focus groups and five individual interviews were conducted with affected family members ( N  = 19). The sample was drawn from a UK-based charity, Cardiac Risk in the Young. Audio-recordings of the focus groups and interviews were transcribed and subjected to thematic analysis. Results: Three super-ordinate themes were identified: 1. YSCD community support as offering a place of safety, 2. YSCD community support as fostering sense-making, 3. YSCD community support as facilitating finding new meaning. Conclusions: YSCD-affected families can benefit from access to dedicated community and peer support that offers a safe environment, provides affiliation, understanding and normalisation and enables sense-making and the rebuilding of a sense of self. Dedicated community support can facilitate meaningful re-engagement with life through helping prevent YSCD and through memorialisation and legacy-building to maintain a continuing bond with the deceased. Clinicians need to be aware of the need to incorporate available community and peer support into patient pathways.